2019
DOI: 10.1111/liv.14083
|View full text |Cite
|
Sign up to set email alerts
|

Lactate and number of organ failures predict intensive care unit mortality in patients with acute‐on‐chronic liver failure

Abstract: Background and Aims:Patients with acute-on-chronic liver failure (ACLF) have high mortality rates. Most prognostic scores were not developed for the intensive care unit (ICU) setting. We aimed to improve risk stratification for patients with ACLF in the ICU. Methods:A training set with 240 patients with cirrhosis and organ failures (Chronic was used to derive a prognostic model for ICU mortality. A validation set with 237 patients with cirrhosis and organ failures from Vancouver General Hospital (Canada) in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 26 publications
1
35
0
3
Order By: Relevance
“…Most patients had infection, sepsis, and even multi-organ failures at ICU admission. A recent multicenter study revealed that ICU and hospital mortality rates in critically ill patients with ACLF were 39.2% and 54.6%, respectively [15]. The hospital and 1-year mortality of patients with ACLF in our study were 49.1% and 63.9%.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Most patients had infection, sepsis, and even multi-organ failures at ICU admission. A recent multicenter study revealed that ICU and hospital mortality rates in critically ill patients with ACLF were 39.2% and 54.6%, respectively [15]. The hospital and 1-year mortality of patients with ACLF in our study were 49.1% and 63.9%.…”
Section: Discussionmentioning
confidence: 42%
“…Several scoring systems incorporating lactate levels have been established to evaluate the prognosis of patients with cirrhosis and ACLF [1518]. The liver injury and failure evaluation (LiFe) score, which is calculated using arterial lactate, serves as a useful tool for predicting the mortality of critically ill patients with cirrhosis and ACLF [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring of lactate levels is important in ICU patients with sepsis [ 23 , 24 ]. The liver accounts for 70% of lactate clearance in the human body [ 25 ], and several studies have focused on the importance of lactate and lactate clearance in critically ill patients with cirrhosis and in ACLF patients [ 7 , 8 , 26 , 27 ]. Some studies proved that using lactate level could improve the accuracy of the traditional model, and constructed improved models like CLIF-C ACLFs Lact [ 8 ] and MELD-LA [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that lactate levels have good predictive value in critically ill patients with cirrhosis [ 7 9 ], and several traditional models were improved by adding lactate, such as CLIF-C ACLFs Lact [ 8 ]. However, most of the models are too complex to use at bedside.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with liver failure due to abnormal liver function rather than causes such as acetaminophen overdose or viral attack usually experience metabolic disorders, acid-base imbalances, decreased liver function over time, and decreased metabolism, which result in recycling and accumulation of lactate. The level of lactate in serum has become an important objective indicator to evaluate the prognosis of patients with cirrhosis and liver failure [40][41][42]. In addition, it has been shown that the rate of lactate clearance is a good and independent predictor of death in critically ill patients with cirrhosis and acute-on-chronic liver failure (ACLF) [43].…”
Section: Discussionmentioning
confidence: 99%